Kepemimpinan Visioner Kiai Zia Ul Haramein dalam Pengelolaan Pesantren di Era Transformasi Digital - Ma’shum, Muhammad Ali; Muhyi, Asep Abdul (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This research analyzes the crucial role of KH. Zia Ul Haramein's visionary leadership in integrating digital technology at Pondok Pesantren Darus Sunnah, exploring solutions for digitalization challenges, and identifying supporting and inhibiting factors for its implementation. Employing a qualitative case study method, with data collected through observation, interviews, and document analysis, this study applies Burt Nanus's theory of visionary leadership. The findings indicate that successfully guided the pesantren's digital technology integration through key leadership roles and adaptive human resources support. This research confirms that visionary leadership can be an effective model for managing the digital transformation of traditional educational institutions without sacrificing noble Islamic values.